Development of Illustrated Story-Based Arabic Teaching Materials for Listening and Speaking Skills - Luthfiatunnisa' Mahiroh; Faiq Ainurrofiq; Yufridal Fitri Nursalam (UIN Sunan Gunung Djati Bandung, 2026)
This research is motivated by the limitations of Arabic language teaching materials that integrate text, images, and audio in learning. Although pictorial media has been used, the integration of picture stories with audio features in one learning design is still limited. This study aims to develop picture story-based Arabic language teaching materials and test their effectiveness in improving students' istima' and kalam skills. This study uses the Research and Development (R&D) method with the Borg and Gall model. The subjects of the study were grade VIII students of MTs Muhammadiyah 6 Ponorogo. Data collection techniques included tests, questionnaires, observations, interviews, and documentation, which were analyzed quantitatively and descriptively. The results showed that the developed product consisted of picture story text, vocabulary, qawaid, exercises, and QR Code containing audio, with a coverage of four chapters for two semesters. The validation results showed that the teaching materials were very valid according to material experts (81.6%) and media experts (87.24%), and received very good student responses (89%). The results of the effectiveness test showed a significant increase with an N-Gain value of 0.73 (high category) and a Sig. 0.000 < 0.05. This research contributes to the development of Arabic language teaching materials that integrate illustrated stories with QR Code-based audio features as an interactive and contextual learning medium to improve students' istima' and kalam skills.